Development of Attention to Faces during the First 3 Years: Influences of Stimulus Type - Libertus, Klaus; Landa, Rebecca J.; Haworth, Joshua L. (Frontiers in Psychology, 2017)
The development of attention toward faces was explored during the first three years of life in 54 children aged between 3 and 36 months. In contrast to previous research, attention to faces was assessed using both static images and a dynamic video sequence in the same participants. Separate analyses at each age and exploratory longitudinal analyses indicate a preference for faces during the first year, followed by a decline during the second year. These results suggest that attention to faces does not follow a linear increasing pattern over development, and that social attention patterns are influenced by stimulus characteristics.